2021
DOI: 10.1136/archdischild-2021-322881
|View full text |Cite
|
Sign up to set email alerts
|

Single versus continuous sustained inflations during chest compressions and physiological-based cord clamping in asystolic lambs

Abstract: BackgroundThe feasibility and benefits of continuous sustained inflations (SIs) during chest compressions (CCs) during delayed cord clamping (physiological-based cord clamping; PBCC) are not known. We aimed to determine whether continuous SIs during CCs would reduce the time to return of spontaneous circulation (ROSC) and improve post-asphyxial blood pressures and flows in asystolic newborn lambs.MethodsFetal sheep were surgically instrumented immediately prior to delivery at ~139 days’ gestation and asphyxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several post-transitional piglet studies demonstrated reduced time to ROSC (between 60% and 75%) and improved mortality in asphyxiated piglets with CC+SI compared with 3:1 C:V 22 25 26. These findings were not replicated, however, in neonatal lamb models 27 28. The differences in the models, most notably the shape of the chest and the method of providing CC in lambs (ie, compression of side of chest or abdominal compressions), have played a significant role in why CC+SI did not show respiratory or haemodynamic benefits over 3:1 C:V in the newborn lamb model 29 30.…”
Section: Chest Compression With Sustained Inflations (Cc+si)mentioning
confidence: 99%
“…Several post-transitional piglet studies demonstrated reduced time to ROSC (between 60% and 75%) and improved mortality in asphyxiated piglets with CC+SI compared with 3:1 C:V 22 25 26. These findings were not replicated, however, in neonatal lamb models 27 28. The differences in the models, most notably the shape of the chest and the method of providing CC in lambs (ie, compression of side of chest or abdominal compressions), have played a significant role in why CC+SI did not show respiratory or haemodynamic benefits over 3:1 C:V in the newborn lamb model 29 30.…”
Section: Chest Compression With Sustained Inflations (Cc+si)mentioning
confidence: 99%
“…Neonatal resuscitation guidelines recommend a 3:1 compression:ventilation (C:V) ratio based on expert opinion, consensus and extrapolation from animal data, rather than strong scientific evidence from clinical studies 1 4. Animal studies have compared C:V ratios (eg, 2:1, 4:1, 9:3 or 15:2) or continuous CC with asynchronised ventilation5–12; however, neither resulted in shorter time to return of spontaneous circulation (ROSC) or reduced mortality. Over the last decade, we have examined continuous CC superimposed by a high distending pressure (termed sustained inflation, SI).…”
Section: Introductionmentioning
confidence: 99%